Perencanaan Video Production dan Talent Agency "Eblo Production" - Jennifer Angelina; Ellen Saputra (Jurnal Vicidi, 2017)
The development of technology such as mobile phones currently affect people's behavior. Almost everything can be accessed via mobile phones whenever and wherever. It’s also affects the function of other technologies, such as TV. Usefulness TV as entertainment is now rarely used, because online sites more accessible, one of which is Youtube. This research aims to design video production along with talent agencies to Youtube. These businesses create entertainment and commercial online. The design process also covers the phase of data collection such as interviews, literature studies, articles, and questionnaires.